Long-Term Efficacy of Vismodegib After its Withdrawal and Patients' Health-Related Quality of Life Using the Dermatology Life Quality Index (DLQI) - Alessia Villani; Matteo Megna; Gabriella Fabbrocini; Milena Cappello; Maria Antonietta Luciano; Claudia Costa; Massimiliano Scalvenzi (Adis, Springer Healthcare, 2019)
Abstract Introduction Although non-melanoma skin cancers (NMSCs) are associated with a very low mortality risk, they have been reported to have a major impact on patients' health-related quality of life (HRQoL). Vismodegib is a therapy for patients who are affected by locally advanced basal cell carcinoma (BCC) or metastatic BCC who are ineligible for surgery and/or radiotherapy. The aim of the present clinical study was to assess the long-term efficacy of vismodegib after its withdrawal by evaluating the recurrence rate of advanced BCC, assessing also patients' HRQoL after 3 and 6 months from drug withdrawal. Methods A retrospective study was performed to analyze patients with advanced and/or multiple BCCs that had been treated with vismodegib (150 mg daily) at the Non-Melanoma Skin Cancer Unit of the University of Naples Federico II (Italy) and had obtained a complete regression in 6 months. At the end of the 6-month treatment cycle, patients that reported total remission of the skin tumor were visited monthly in order to assess their therapeutic response. Moreover, to assess the specific impact of vismodegib on HRQoL, DLQI was administered before vismodegib treatment (baseline), at the end of the therapy cycle (6 months), as well as after 3 and 6 months from vismodegib discontinuation. Results Thirty-five patients (27 male, 8 female), with a complete regression of their advanced BCC after vismodegib treatment, were included in the study. The duration of treatment for all patients was 6 months as set by study inclusion criteria. A BCC recurrence rate of 31% (11/35) was reported after a 6-month follow-up. The average reported Dermatology Life Quality Index (DLQI) score increased from a value of 0 at the end of the 6-month vismodegib treatment to a mean value of 2.4 after 3 months from drug withdrawal and 3.6 after 6 months from treatment discontinuation. Conclusion The results of this exploratory analysis of vismodegib withdrawal are consistent with a substantial link between treatment response and patients' HRQoL. Furthermore, 11 out of 35 (31%) patients that reported a complete remission of the disease after 6 months of vismodegib treatment reported BCC recurrence. These data highlight the importance of continuous follow-up and perhaps different regimens of treatment, such as an alternate dose regimen to maintain disease control and reduce the adverse events as previously described in the literature.